AXL Promotes Metformin-Induced Apoptosis Through Mediation of Autophagy by Activating ROS-AMPK-ULK1 Signaling in Human Esophageal Adenocarcinoma - Hong, Jun; Maacha, Selma; Pidkovka, Nataliya; Bates, Andreia; Salaria, Safia N.; Washington, Mary K.; Belkhiri, Abbes (Frontiers in Oncology, 2022)
AXL receptor tyrosine kinase promotes an invasive phenotype and chemotherapy resistance in esophageal adenocarcinoma (EAC). AXL has been implicated in the regulation of autophagy, but the underlying molecular mechanism remains poorly understood. Herein, we investigate the mechanistic role of AXL in autophagy as well as metformin-induced effects on the growth and survival of EAC. We demonstrate that AXL mediates autophagic flux through activation of AMPK-ULK1 signaling in a reactive oxygen species (ROS)-dependent mechanism by glucose starvation. AXL positively regulates basal cellular ROS levels without significantly affecting mitochondrial ROS production in EAC cells. Pharmacological inhibition of cellular ROS using Trolox abrogates glucose starvation-induced AMPK signaling and autophagy. We demonstrate that AXL expression is required for metformin-induced apoptosis in EAC cells in vitro. The apoptosis induction by metformin is markedly attenuated by inhibition of autophagy through genetic silencing of Beclin1 or ATG7 autophagy mediators, thereby confirming the requirement of intact autophagy for enhancing metformin-induced apoptosis in EAC cells. Our data indicate that metformin-induced autophagy displays a pro-apoptotic function in EAC cells. We show that the metformin-induced suppression of tumor growth in vivo is highly dependent on AXL expression in a tumor xenograft mouse model of EAC. We demonstrate that AXL promotes metformin-induced apoptosis through activation of autophagy in EAC. AXL may be a valuable biomarker to identify tumors that are sensitive to metformin. Therefore, AXL expression could inform the selection of patients for future clinical trials to evaluate the therapeutic efficacy of metformin in EAC.